Smart Controller Placement for Uninterrupted Software Defined Networking Service under DDoS Attack in RF, Data Center and Telecom Industries - et al., Muhammad Reazul Haque (International Journal of Advanced Science and Technology, 2019)
In software defined networks (SDN) controller placement is essential and it’s a critical issue. Existing research works address the primary factors, such as reliability, latency, capacity of controllers, propagation delay of control paths and energy consumption etc. In this paper, we propose an integer linear programming (ILP) scientific model for the controller position in SDN due to DDoS attack. More unerringly, conferred a set of switches that must be overseen by the controller(s), our proposed model can decides the ideal number, node, and kind of unique and smart controller(s) just as the interconnections between all the system components under DDoS attack simultaneously. The objective of the model is to limit the absolute expense without compromising the continuous service of SDN while considering different scenarios of DDoS attack .The simulated results obtained demonstrate that the ILP scientific model can be utilized to design and plan small and medium scale SDN